Synthesis and evaluation of antibacterial and antioxidant activity of novel 2-phenyl-quinoline analogs derivatized at position 4 with aromatically substituted 4H-1, 2, 4-triazoles. (2nd November 2016) - Verbanac, Donatella; Malik, Ritu; Chand, Mahesh; Kushwaha, Khushbu; Vashist, Monika; Matijašić, Mario; Stepanić, Višnja; Perić, Mihaela; Paljetak, Hana Čipčić; Saso, Luciano; Jain, Subhash C.
Abstract: A set of novel quinolone–triazole conjugates (12 –31 ) were synthesized in three steps in good yields starting from 2-phenylquinoline-4-carboxylic acid. All the intermediates, as well as the final 1, 2, 4-triazolyl quinolines were fully characterized by their detailed spectral analysis utilizing different techniques such as IR, 1 H NMR, 13 C NMR, and finally mass spectrometry. All the synthesized compounds were evaluated in vitro for their potential antibacterial activity and their preliminary safety profile was assessed through cytotoxicity assay. Additionally, six selected conjugates were evaluated for their antioxidative properties on the basis of density functional theory calculations, using radical scavenging assay (DPPH) and cellular antioxidant assay. The reported results encourage further investigation of selected compounds and are shading light on their potential pharmacological use.